Pivot Bio Proven Inoculant as a Source of Nitrogen in Corn - William G. Davis; Carlos A. Bonini Pires; Dorivar A. Ruiz Diaz; Kraig L. Roozeboom; Charles W. Rice (Kansas Agricultural Experiment Station Research Reports, 2020)
Nitrogen (N) fertilizer represents a significant annual cost for farmers. Additionally, N losses pose environmental concerns and represent loss of resources. Proven, an N fixing bacterial inoculant for corn developed by Pivot Bio (Berkeley, CA) is expected to fix between 20 and 30 lb N/a over a growing season. The use of bacterial inoculants to fix N for corn reduces the risk of N loss through leaching and volatilization by reducing the amount of inorganic fertilizers required to maximize yield. To evaluate the efficacy of Proven, a field trial was established in Manhattan, KS, on a Kennebec silt loam that had been under continuous no-till corn production for 5 years. The experiment was arranged in a split-plot design with four replications. The main treatment was N fertilizer rate at 0, 50, 100, and 150 lb N/a applied as urea directly before planting. The subplot factor was with and without Proven. Soil samples were taken before planting (0–36 in.), at V6 (0–12 in.), R1 (0–12 in.), and harvest (0–36 in.) for inorganic N. Plant measurements included vigor at V4 and V8-V10; NDVI at V5-V8; SPAD readings at R1-R3; and green leaf counts during grain fill. Whole plant biomass and N content were determined at R6. At harvest, grain moisture, test weight, and yield were measured. Nitrogen rate significantly affected grain yield and plant N uptake. The effect of Proven was not significant nor was the interaction between N rate and Proven.
Keywords: bacteria; nitrogen fixation; cereal crop